Use of ceramic material from BDW for concrete application: a review - Silva, Danillo Almeida e; Melo, Carlos Eduardo Luna de (Risco - Journal of Architecture and Urbanism, 2021)
Solid waste, produced from construction and demolition activities, reaches several million tons daily. Among these residues, the ceramic material "bricks, tiles and ceramic tiles" is among the most abundant. In recent years, numerous researches have been carried out to produce more environmentally friendly concrete. The use of ceramic waste as coarse and fine aggregate for the production of concretes is one of the commonly researched approaches, however recent research is studying the feasibility of using ceramic powder as a substitute for cements for the production of concretes. The results indicate that the substitution of cement by red ceramic powder can improve some properties of concrete, due to the potential of pozzolanic reactivity of ceramic powder particles.